Phase Change Material (PCM) as the Smart Heat-Storing Concept: A Brief Review - Payam Nejat; Yashar Fekri; Fatemeh Jomehzadeh (Annals of Marine Science - Peertechz Publications, 2022)
Recently smart materials play an important role in different aspects of the industry due to their specific characteristics. The properties of these materials can change spontaneously in interaction with the immediate surrounding without any external power consumption. Phase change materials are a great division of smart materials with considerable capacity to absorb and release thermal energy during the phase change process. They can also handle temperature regulations since the phase change process occurs at a constant temperature. The implementation of PCMs is one of the potential passive cooling strategies which has received increasing attention in recent years. This paper aims to briefly review the various types of PCMs which can be used for passive cooling in buildings.